Fenomena Budaya Populer K-Pop Dalam Komunikasi Identitas Diri Komunitas Bts Army Pada Generasi Milenial Di Kota Kendari - andi juliana; Mahdar .; Ashar Hasyim (Jurnal Ilmu Komunikasi Dan Sosial Politik, 2026)
This study discusses the main issue of the influence of BTS K-Pop culture on the formation of self-identity of the Millennial Generation ARMY community in Kendari City, which challenges the assumption that K-Pop fans are limited to teenagers. The goal is to uncover the communication process that shapes this identity in the group born 1981-1996. A qualitative method with a phenomenological approach was used, collecting data from 6 informants (1 admin, 5 married members) through observation, in-depth interviews, and documentation, analyzed through data reduction, presentation, and drawing conclusions. The results show that identity is formed through Michael Hecht's four theoretical frameworks: personal frames (the value of hard work, self-love), enacted frames (fandom language, Korean fashion, social media), relational frames (emotional bonds between members), and communal frames (global social-charity participation). K-Pop influences verbal-nonverbal language, lifestyle, and mindset, supported by social media, community interactions, idol messages, and family.